Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) Co-infection among HIV infected individuals at tertiary care hospital in western Nepal - Supram, Hosuru Subramanya; Gokhale, Shishir; Sathian, Brijesh; Bhatta, Dharma Raj (Nepal Journal of Epidemiology, 2015)
Background: The HIV, HBV and HCV viruses are the major public health concern all over the world including Nepal. The aim of the study is to determine the rate of HBV and HCV co-infections in patients with HIV infection. Methods: The study cohort included 218 consecutive HIV infected patients who were examined for co-infection with HBV or HCV or both at Manipal teaching hospital, Western Nepal. The demographic data of the subjects was collected retrospectively. The data was analyzed with SPSS software and EPI Info to measure the correlation of variables and infection rates. Results: In the course of six years study period, a total of 25,708 samples were collected for HIV screening test. The 218 (0.8%) screen test positive for HIV were confirmed as per WHO guidelines. The overall rate of co-infection with HBV and or HCV was 7.3% (16 of 218 patients). Only 7 (3.2% [CI 1.3, 6.5]) were positive for both HIV and HBV infection markers and 9 (4.1% [CI 1.9, 7.7]) were positive for HIV and HCV infection markers. None were positive of all three virus markers. Conclusion: It is advisable to implement regular screening for Hepatitis B Virus and Hepatitis C Virus among all HIV infected individuals and their sexual partners. DOI: http://dx.doi.org/10.3126/nje.v5i2.12831 Nepal J Epidemiol. 2015;5(2); 488-493.